Integrative taxonomy of Metastrongylus spp. in wild boars from Brazil - Oliveira, Wilson Junior [UNESP]; Perin, Patricia Parreira [UNESP]; Arias Pacheco, Carmen Andrea [UNESP]; Mendonça, Talita Oliveira [UNESP]; de Souza Pollo, Andressa [UNESP]; do Amaral, Renan Bressianini; de Oliveira Zolla, Natália [UNESP]; de Oliveira Andrade, Lívia [UNESP]; Gomes, Jonathan Silvestre [UNESP]; dos Santos, Vitória Maximiana Soares [UNESP]; de Moraes Ferreira, Adrian Felipe [UNESP]; Lux Hoppe, Estevam Guilherme [UNESP] (Springer Nature, 2023)
Background: Wild boars (Sus scrofa) may cause substantial damage to crops and can spread zoonotic parasites to domestic animals, posing a risk to health and animal production. Metastrongylus spp. can negatively affect the wild boar population, increasing piglet mortality. In addition to that, studies with Metastrongylus genetic characterization are still scarce in Brazil. The present study aims to characterize Metastrongylus spp. from wild boars hunted in the states of São Paulo, Paraná, and Rio Grande do Sul, Brazil, using traditional morphological description and DNA sequences in an integrative taxonomic approach. Methods: After nematode collection from 58 wild boars, the parasites were morphologically identified and genetically characterized by the amplification of 18S ribosomal DNA (rDNA), 28S rDNA, internal transcribed spacer (ITS) region, and cox-1 mitochondrial DNA (mtDNA). Descriptors of infection were determined and Pearson's Chi-square test was applied to compare the prevalence of infections among the identified parasite species, host age group (juveniles and adults), and sex. The Mann–Whitney U test was performed to compare the mean intensity between the age groups and sex. Results: Metastrongylus salmi, Metastrongylus apri, and Metastrongylus pudendotectus were identified in 77.6% (45/58) of the necropsied wild boars. Metastrongylus salmi was the most prevalent and abundant species (70.7%, 11.1), followed by M. pudendotectus (18.9%, 4.3) and M. apri (17.2%, 2.2). Metastrongylus pudendotectus showed the highest mean intensity and range (25.2, 1–93), followed by M. salmi (15.7, 1–58) and M. apri (12.6, 3–27). We found a significantly higher prevalence of Metastrongylus spp. and M. salmi in adult wild boars, probably associated with a more prolonged time of exposure to intermediate host species. The phylogenetic analysis revealed that ITS2 region and cox-1 mtDNA are the most suitable genetic markers for Metastrongylus species characterization. Genetic variability between M. apri and M. salmi isolates was verified. Conclusions: We expand the knowledge about the Metastrongylus community in the non-captive wild boar population from Brazil as well as the importance of this exotic species in the maintenance of Metastrongylus spp. in its areas of occurrence. The novel genetic sequences obtained may help further studies to understand the genetic diversity in other nematode populations from Brazil and other countries. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Invasive species; Lungworms; Metastrongylus; Morphology; Neotropical region; Phylogeny